An evaluation of community pharmacy-based services for type 2 diabetes in an Indonesian setting: patient survey - Yosi Wibowo; Richard Parsons; Bruce Sunderland; Jeffery Hughes (PeerJ, 2015)
Background. Diabetes is an emerging chronic disease in developing countries. Its management in developing countries is mainly hospital/clinic based. The increasing diabetes burden in developing countries provides opportunities for community pharmacists to deliver a range of services. Since the management of diabetes requires the patient’s own involvement, it is important to gain their views in order to develop pharmacy-based diabetes services. Studies on diabetes patients’ views have been limited to developed countries.Objectives. To investigate, within a developing country setting (Indonesia), current use of pharmacy services by type 2 diabetes patients, and to evaluate their views regarding community pharmacists’ roles, and the characteristics that influence their views.Methods. A questionnaire survey was conducted within 10 purposefully selected community pharmacies in Surabaya, Indonesia. Each pharmacy recruited approximately 20 patients seeking antidiabetic medications. Usage of pharmacy services was identified using binary responses (‘yes’/‘no’) and views on pharmacists’ roles were rated using Likert scales; an open-ended question was used to identify patient perceived priority roles. Logistic regression models were used to determine characteristics associated with patients’ views.Results. A total of 196 pharmacy patients with type 2 diabetes responded (58.3% response rate). Most patients used community pharmacies for dispensing (100%) and education on how to use medications (79.6%). There were mixed views towards pharmacists providing services beyond dispensing. The highest priorities identified were from the ‘patient education’ domain: education on medications (i.e., directions for use (64.5%), storage (26.6%), common/important adverse effects (25.5%)); and the ‘monitoring’ domain: monitoring medication compliance (37.3%). Patients with higher incomes or who were working were less supportive of these expanded services, whereas patients who previously used a service, those with risk factors for complications or having poor/unknown glycaemic control were more supportive.Conclusions. Community pharmacies in Surabaya, Indonesia in this study were mainly utilised for dispensing. However, many type 2 diabetes patients using these pharmacies report limited monitoring of blood glucose levels and poor glycaemic control, which indicates an opportunity for greater pharmacist involvement. Yet for this to occur, patients’ limited expectations of pharmacists roles will need to be broadened. Characteristics influencing these views should inform the development of pharmacy-based diabetes services in the environment of the burgeoning burden of diabetes.